2022
DOI: 10.1177/09544097221076258
|View full text |Cite
|
Sign up to set email alerts
|

Carrydown of liquid friction modifier

Abstract: A small-scale laboratory apparatus was built to study liquid friction modifier (LFM) behavior in a top-of-rail application. A field experiment was also carried out to complement the laboratory findings. KELTRACK® (a water-based LFM) was used as the test fluid. Laser-induced fluorescence served to measure the LFM thickness left on the track after the passage of the wheel. The lab experiments show that the LFM cannot withstand the high wheel-rail contact pressure in the nip present in cargo rail situations. As a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…One laboratory-based study has been carried out on TOR product pick-up, 17 but in this work, friction was not measured and mechanisms of pick-up/carry-down were not explored in detail. Recently field studies carried out have shown that TOR products do not appear to be carried down more than a few hundred metres on the rail 18,19 From this work, however, indications were that the product on the wheel could be effective for >3 km. This ties-up with lateral force measurements that have shown that TOR products have an effect 3 km from application.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…One laboratory-based study has been carried out on TOR product pick-up, 17 but in this work, friction was not measured and mechanisms of pick-up/carry-down were not explored in detail. Recently field studies carried out have shown that TOR products do not appear to be carried down more than a few hundred metres on the rail 18,19 From this work, however, indications were that the product on the wheel could be effective for >3 km. This ties-up with lateral force measurements that have shown that TOR products have an effect 3 km from application.…”
Section: Introductionmentioning
confidence: 66%
“…For example, a 35% lateral force reduction was detected 3 km from the application point of a TOR-FM in field trial described previously. 19 While detection of product on the rail head can be achieved, checking wheels is difficult in normal field trials as the trains pass and go. In a recent track trial, using a locomotive running through the same puddle of product repeatedly, with the same lateral position for the wheels, 18 it was shown that product could only be detected using a swabbing technique for up to 450 m down the track.…”
Section: Discussionmentioning
confidence: 99%